Penerapan Model Kano Dengan Menggunakan Dimensi Serqvqual Dalam Upaya Peningkatan Kualitas Layanan Web Di Sekolah Tinggi XYZ - Dorie Pandora Kesuma; Rika Kharlina Ekawati (Universitas Katolik Musi Charitas, 2018)
Today, web-based electronic services are usually applied by various higher education institutions in effort to meet the interests of the organization and also the interests of their service users. This research use Kano Model to study service quality attributes found on the website services of higher education institutions at XYZ Higher Education so that the management of XYZ Higher Education can know the priority needs of their web-based service users to improve the quality of the its web-based services. The Kano Model is also used to measure the relationship between the level of satisfaction and the effort to improve it’s level by XYZ Higher Education. This research use 27 service quality attributes that were measured using the Kano Model. The results of this research showed that from 27 attributes, 11 attributes were eliminated and other 16 attributes need to be improved and maintained.